(untitled) (Journal of Nepal Physical Society, 2022)
After significant solar eruptions, protons are fired at extremely high speeds, sometimes reaching several thousand kilometer per second (km/s), resulting in solar radiation storms. Solar particle events can be found all around the heliosphere. The cross-correlation analysis along with time series analysis is used to look at how the solar wind and proton flux are related. The parameters used in this work are flux of Solar Energetic Protons (SEP) ranging from >10 MeV to >60 MeV along with speed, density, and pressure of the solar wind parameters. The findings indicate that proton flux (E>10 MeV) shows significant changes just before the storm while flux (E>30 MeV) and (E>60 MeV) doesn’t correlate with solar parameters although during quiet day no significant changes were observed. These finding suggested that SEP can be used as precursor of CME driven storms.